2020
DOI: 10.1088/1755-1315/593/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction Characteristics of Tropical Eel Anguilla bicolor McClelland in Different Developmental Stage

Abstract: The reproductive characters provide information about the gonad maturity of eel. The prepubertal stage occurs in the yellow eel, and the pubertal stage achieves in the silver eel. This study aimed to evaluate the reproductive characters of tropical eel, Anguilla bicolor McClelland in the different developmental stages. Eels with 33 - 81 cm ± 13.54 length, and weight of 98 - 1062 g ± 262.99 were used to determine their reproductive characters. The variables observed were the total length, body weight, Gonadosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…These results were consistent with an earlier study that reported a lower GSI of A. bicolor collected in an estuary environment (Hagihara et al, 2020). Other sources stated GSI values ranging from 1.04 to 2.96%, 0.1 to 2.88% (Rachmawati and Susilo, 2009;, and 0.03 to 4.37% (Rachmawati and Sistina, 2020) for similar species, which were comparable to the values obtained in this current study. Lower GSI values suggested that A. bicolor gonads were still in the immature stage, as opposed to A. japonica, found with a GSI of 4.3% at the pubertal stage (Kotake et al, 2005).…”
Section: Resultssupporting
confidence: 93%
“…These results were consistent with an earlier study that reported a lower GSI of A. bicolor collected in an estuary environment (Hagihara et al, 2020). Other sources stated GSI values ranging from 1.04 to 2.96%, 0.1 to 2.88% (Rachmawati and Susilo, 2009;, and 0.03 to 4.37% (Rachmawati and Sistina, 2020) for similar species, which were comparable to the values obtained in this current study. Lower GSI values suggested that A. bicolor gonads were still in the immature stage, as opposed to A. japonica, found with a GSI of 4.3% at the pubertal stage (Kotake et al, 2005).…”
Section: Resultssupporting
confidence: 93%
“…Female A. bicolor is more dominant caught in freshwater than an estuary; the results of this study are the same as the observations of [12] and [23]. Female of A. bicolor has a 100% dominant catch in Segara Anakan [12].…”
Section: Sex Ratiosupporting
confidence: 87%
“…Female of A. bicolor has a 100% dominant catch in Segara Anakan [12]. In contrast, in Peninsular Malaysia, 73% females, 13% of males, and 14% of gonads undifferentiated [23].…”
Section: Sex Ratiomentioning
confidence: 99%
“…It also has plain body skin [10]. The eel stage in this study was classified based on [11] and [12] studies. Tesch [11] classified an elver stage as the eel with a length greater than 7 cm, [12] grouped the yellow eel stage as the eel with a length of 20-45 cm, and eels with a size greater than 45 cm are in the adult/silver eel stage [13].…”
Section: Methodsmentioning
confidence: 99%